A study of C reactive proteins in patients with stable chronic obstructive pulmonary disease - Gudagunti, Ashok Kumar; Chaudhri, Sudhir (International Journal of Advances in Medicine, 2019)
Background: Whenever there is damage to the tissue or inflammatory process, the hepatocytes synthesize a protein which is an acute phase reactant, and this is the C reactive protein. Studies have shown that serum C reactive protein levels are usually elevated during acute exacerbations of COPD. The objective of this study was studying the baseline serum C reactive protein levels in patients with stable chronic obstructive pulmonary disease. Methods: During the study period, 90 subjects were studied. Out of them, 47 had stable COPD and 43 were without COPD. The subjects were either admitted in indoor wards or were attending OPD of department of tuberculosis and respiratory diseases, Dr. Murari Lal Chest Hospital, G.S.V.M Medical College, Kanpur, Uttar Pradesh, and were recruited if they fulfilled the criteria for inclusion. Informed consent was taken from all study subjects and the study protocol was approved by the board of faculty of medicine. Results: Of the 47 patients in the stable COPD group, 23 were found to be active smokers. Pearson’s correlation coefficient showed that lower limit of serum CRP levels were significantly negatively correlating with 6 MWD (r= -0.707; p=0.0001), FEV1% (r=-0.635; p=0.0001), PaO2 (r=-0.592; p=0.0001), and BMI (r= -0.534; p=0.0001). Pearson’s correlation coefficient showed that upper limit of serum CRP levels were significantly negatively correlating with 6 MWD (r= -0.707; p=0.0001), FEV1% (r= -0.633; p=0.0001), PaO2 (r= -0.61; p=0.001) and BMI (r= -0.520; p=0.0001). Conclusions: The circulating levels of inflammatory marker, baseline serum CRP are significantly elevated in patients with stable chronic obstructive pulmonary disease.